A thin CdSe shell boosts the electron transfer from CdTe quantum dots to methylene blue. Issue 4 (12th January 2018) - Dworak, L.; Roth, S.; Scheffer, M. P.; Frangakis, A. S.; Wachtveitl, J.
Abstract : The CdSe coating of CdTe nanocrystals produces quasi type-II quantum dots with improved charge transfer properties. Abstract : CdTe core and CdTe/CdSe core/shell quantum dots (QD) are investigated with steady state and time-resolved spectroscopic methods. The coating of the CdTe core with a 0.7 nm thick CdSe shell shifts the lowest exciton absorption band to the red by more than 70 nm making the CdTe/CdSe QD an interesting candidate for application in solar energy conversion. Femtosecond transient absorption measurements are applied to study the photoinduced electron transfer (ET) to the molecular acceptor methylene blue (MB). ET times after single excitation of the QD are determined for different MB : QD ratios. The ET reaction is significantly faster in the case of the MB–CdTe/CdSe QD complexes, indicative of an altered charge distribution in the photoexcited heterostructure with a higher electron density in the CdSe shell. As a result of the efficient absorption of incoming light and the faster ET reaction, the amount of reduced MB in the time resolved experiments is higher for CdTe/CdSe QD compared to CdTe QD.